BNT‐based ferroelectric ceramics: Electrical properties modification by Ta2O5 oxide addition. Issue 1 (4th September 2019) - Han, Jihui; Yin, Jie; Wu, Jiagang
Abstract: Due to their superior piezo‐responses (strain S > 0.3%), bismuth sodium titanate (BNT)‐based relaxor ferroelectrics have received much attention. Compared to other chemical elements, tantalum (Ta) doping provides superior electro‐strain for these ferroelectrics, while the effect of Ta2 O5 as oxide additive has been rarely reported. Herein, lead‐free piezoceramics of Bi0.5 (Na0.72 K0.22 Li0.06 )0.5 TiO3 ‐ x Ta2 O5 (BNKLT‐ x Ta2 O5, x = 0‐0.015) are synthesized. We study the effects of Ta2 O5 addition on the crystal structure, piezoelectric responses, dielectric properties, and ferroelectric properties of BNKLT ceramics. All of the ceramics exhibit a typical perovskite structure, and Ta2 O5 diffuses into the BNKLT lattice to form a uniform solid solution. The addition of Ta2 O5 can make the grains more regular and uniform, while excess Ta2 O5 result in finer grains. The undoped BNKLT ceramics show good ferroelectric and piezoelectric properties (remnant polarization P r = 22.5 μC/cm 2 and piezoelectric coefficient d 33 = 250 pC/N); however, the addition of Ta2 O5 leads to an clear degradation in d 33 and P r . Meanwhile, the addition of an appropriate Ta2 O5 amount leads to an increase in the electro‐strain, and the unipolar strain reaches 0.385% under 60 kV/cm for x = 0.003, together with a higher normalized strain ( d 33 * = S max / E max ) of 633 pm/V ( x = 0.003). The enhanced strain behaviors can be attributed to the coexistence of the ferroelectric and relaxor states, and an excellent electrostriction coefficient Q 33 ( Q 33 = S / P 2 ) value of 0.038 m 4 C −2 is obtained under 60 kV/cm for x = 0.003.